1987
DOI: 10.1016/0014-5793(87)80240-5
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine agonists protect a histidine residue from modification by diethyl pyrocarbonate whereas propyl β‐carboline does not

Abstract: The pH sensitivity of benzodiazepine binding suggests that a histidine residue may be present in, or close to the benzodiazepine binding site. This was confirmed by the selective modification of histidine residues using diethyl pyrocarbonate which was found to block both benzodiazepine and β‐carboline binding. In order to assess whether this histidine residue is located in or adjacent to the benzodiazepine and β‐carboline binding sites, experiments were performed using either benzodiazepine or β‐carboline to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The binding of [3H]flunitrazepam and [3H]Ro 15-1788 is sensitive to a pH change from 7.5 to 5.5 (Lambolez and Rossier, 1987;Lambolez et al, 1989). High ionic strength, which diminishes the electrostatic interaction between surface residues of proteins, had no effect on the decrease in binding.…”
Section: Discussionmentioning
confidence: 97%
“…The binding of [3H]flunitrazepam and [3H]Ro 15-1788 is sensitive to a pH change from 7.5 to 5.5 (Lambolez and Rossier, 1987;Lambolez et al, 1989). High ionic strength, which diminishes the electrostatic interaction between surface residues of proteins, had no effect on the decrease in binding.…”
Section: Discussionmentioning
confidence: 97%
“…The photoincorporation of [ 3 H]flunitrazepam with His 102 is consistent with the findings of hydroxylamine cleavage experiments that demonstrated photolabeling occurred prior to Asn 103 , as well as previous reports that predicted the site occurred within limited subunit domains (see Introduction). The involvement of a histidine residue in the interaction of benzodiazepines with the GABA A receptor was implicated in earlier studies that investigated the effects of chemical modification and the pH dependence of radioligand binding (23,24). In addition, His 102 of the ␣ 1 subunit is the residue that was shown by point mutation to be required for the high affinity binding of benzodiazepine agonists in recombinantly expressed GABA A receptors (7).…”
Section: Fig 4 Release Of Radioactivity From Hplc Peaks (I) and (Ii)mentioning
confidence: 97%
“…Because histidine is the only amino acid that has a side-chain pK, in solution between pH 7.5 and 5.5 and because the increase in ionic strength does not shift the decrease in binding at pH values of 4 . 5 , these authors suggested that this decrease is due to the protonation of a histidine residue (Lambolez and Rossier, 1987;Lambolez et al, 1989). In contrast, the binding of [3H]Ro 15-4513 is not decreased between pH 7.5 and 5.5, suggesting that it does not interact with the histidine residue responsible for the decreased binding of the above-mentioned ligands at pH values of <7.5 .…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence for the involvement of a histidine residue in the binding of benzodiazepine receptor ligands is provided by the effect of pH on the binding. The pH optimum of [3H]flunitrazepam and [3H]Ro 15-1788 binding is 7.5, and the binding of both ligands is decreased at lower pH (Lambolez and Rossier, 1987;Lambolez et al, 1989). Because histidine is the only amino acid that has a side-chain pK, in solution between pH 7.5 and 5.5 and because the increase in ionic strength does not shift the decrease in binding at pH values of 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation